2022
DOI: 10.1021/jacs.2c11024
|View full text |Cite
|
Sign up to set email alerts
|

Deoxygenative Haloboration and Enantioselective Chloroboration of Carbonyls

Abstract: Deoxygenative difunctionalization of carbonyls affords a straightforward and effective route to construct geminal dual functionalized motifs. However, the research in this field is very challenging due to the strong bond dissociation energies of the C−O double bond or the subsequently formed C−O bond. Herein, we report a highly efficient deoxygenative haloboration of aldehydes to generate secondary α-haloboronates. Meanwhile, the difficult-to-obtain tertiary α-haloboronates can be also readily prepared via the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 58 publications
0
31
0
Order By: Relevance
“…To this end, very recently, we reported a very convenient and modular method to construct -haloboronates or chiral -chloroboronates via a deoxygenative difunctionalization of carbonyls (DODC) strategy. 23 We found that for the aldehyde (44-a), after the copper-catalyzed borylation, the in-situ formed intermediate can be easily converted into -chloroboronate product (46-a) in 90% yield by simple reaction with TMSCl With these conditions, a diverse set of aldehydes bearing various functional groups, even for those that are sensitive to strong bases or organometallic reagents, can be compatible, thus providing a protocol to synthesize complex skeletons (Scheme 15). Meanwhile, -bromo-and -iodoboronates can be conveniently accessed just by replacing the nucleophile TMSCl with TMSBr or TMSI.…”
Section: Scheme 13 the Preparation Of -Aryl--chloroboronatesmentioning
confidence: 99%
“…To this end, very recently, we reported a very convenient and modular method to construct -haloboronates or chiral -chloroboronates via a deoxygenative difunctionalization of carbonyls (DODC) strategy. 23 We found that for the aldehyde (44-a), after the copper-catalyzed borylation, the in-situ formed intermediate can be easily converted into -chloroboronate product (46-a) in 90% yield by simple reaction with TMSCl With these conditions, a diverse set of aldehydes bearing various functional groups, even for those that are sensitive to strong bases or organometallic reagents, can be compatible, thus providing a protocol to synthesize complex skeletons (Scheme 15). Meanwhile, -bromo-and -iodoboronates can be conveniently accessed just by replacing the nucleophile TMSCl with TMSBr or TMSI.…”
Section: Scheme 13 the Preparation Of -Aryl--chloroboronatesmentioning
confidence: 99%
“…4, 133.2, 130.6, 128.9, 128.1, 121.7, 84.6, 29.6, 24.73, 24.65; 11 4,4,5,5-tetramethyl-1,3,2dioxaborolane (11). Colorless oil; yield 83%, 29.9 mg; 1 H NMR (600 MHz, CDCl 3 ) δ 7.98 (s, 1H), 7.82−7.78 (m, 4H), 7.47−7.45 (m, 2H), 2.25 (s, 3H), 1.32 (s, 12H); 13 C{ 1 H} NMR (150 MHz, CDCl 3 ) δ 141.0, 132. 9,132.5,128.3,127.8,127.4,127.0,126.2,126.1,125.0,84.7,29.1,24.44,24.38;11 B NMR (193 2-(1-Bromo-1-phenylpropyl) -4,4,5,5-tetramethyl-1,3,2-dioxaborolane (12).…”
Section: -[1-bromo-1-(2-chlorophenylmentioning
confidence: 99%
“…Recently, halides (Cl, Br, and I) were used as nucleophiles in the transformation of the C–O bond in tertiary α-OBpin boronates to construct a series of α-haloboronates by the Xu group (Scheme 21). 37 With ketones as substrates, the difficult-to-obtain tertiary α-haloboronates could be readily obtained. Furthermore, chiral secondary or tertiary α-chloroboronates could be obtained successfully via enantioselective chloroboration of carbonyls, and the enantioselectivities and yields of the products obtained from aldehydes were excellent compared to those obtained from ketones.…”
Section: Transformation Of α-Oxylboronate Speciesmentioning
confidence: 99%